1997
DOI: 10.1037/0022-3514.73.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Superstars and me: Predicting the impact of role models on the self.

Abstract: The authors propose that superstars are most likely to affect self-views when they are considered relevant. Relevant superstars provoke self-enhancement and inspiration when their success seems attainable but self-deflation when it seems unattainable. Participants' self-views were affected only when the star's domain of excellence was self-relevant. Relevant stars provoked self-enhancement and inspiration when their success seemed attainable in that participants either still had enough time to achieve comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

80
1,188
5
16

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,232 publications
(1,325 citation statements)
references
References 42 publications
80
1,188
5
16
Order By: Relevance
“…Furthermore, she admired these teachers for respecting the "learning and the learners". These perceptions concerning roleexpectation information and respect for learners suggest similarities concerning pedagogical goals between Veronica and those teachers, and has been reported within the role model literature by Lockwood and Kunda (1997) who suggested that individuals chose role models if they pursued the attainment of similar goals.…”
Section: Adulthood Experiencessupporting
confidence: 65%
See 2 more Smart Citations
“…Furthermore, she admired these teachers for respecting the "learning and the learners". These perceptions concerning roleexpectation information and respect for learners suggest similarities concerning pedagogical goals between Veronica and those teachers, and has been reported within the role model literature by Lockwood and Kunda (1997) who suggested that individuals chose role models if they pursued the attainment of similar goals.…”
Section: Adulthood Experiencessupporting
confidence: 65%
“…This is the case, for example, of ballet, where role modelling has a strong component in teaching (Gray, 1990;Scheff, 2005); nevertheless, a condition that needs to be fulfilled is for the teacher, as a role model, to be competent in transmitting content (Justi & Gilbert, 2002). Role modelling relationships might include mentoring functions (Carruthers, 1990); however, a critical difference between mentoring and role modelling is that in role modelling, role models might not be aware that they are a role model (Lockwood & Kunda, 1997), whereas in a mentoring relationship both mentor and protégé are aware of their status .…”
Section: Role Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a social comparison perspective, Vince considered Allen a target to emulate. This literature would consider Vince's desire to adjust his behavior to achieve the same acknowledgement Allen received "upward social comparison," whereby an individual may selfenhance behavior to improve both self-evaluations and others' perceptions (Hackett, Esposito, & O'Halloran, 1989;Lockwood & Kunda, 1997). From an alternative, social-cognitive perspective, it could be speculated that the nature of feedback from Professor Houston and "significant others" primed (i.e., triggered implicit understanding in) members to learn what was acceptable and unacceptable.…”
Section: Social Comparisonsmentioning
confidence: 99%
“…In fact, contrary to the common view, this drive also entails beneficial effects. Comparing oneself to similar superior others is, notably, one of the motors of self-improvement as it can foster motivation to equal or even surpass the upward standard (Lockwood & Kunda, 1997;Wheeler, 1966). Moreover, people often engage in downward comparisons to feel better about themselves, especially when they feel threatened in their self-esteem (Wills, 1981).…”
Section: Introductionmentioning
confidence: 99%